The Anti-Inflammatory Effects of Mango, Orange, and Dragon Fruit on C-reactive protein (CRP) Levels in a Hypercholesterolemic Rat Model - Zaki, Ibnu; Putri, Widya Ayu Kurnia; Muzadi, Firman (Journal of Health and Nutrition Research, 2025)
Inflammation is a response to tissue injury or infection. Fruits such as mango, oranges, and dragon fruit contain nutrients that can reduce levels of inflammation in the body. This study aimed to investigate the effect of mango, orange, and dragon fruit on C-reactive protein (CRP) levels in experimental animals. This study was conducted using a randomized controlled pre-posttest design with 30 Sprague Dawley rats were divided into five groups, group K1 without treatment, group K2 only received high fat diet (HFD), group K3 received HFD with intervention of gedong gincu mango at a dose of 3.6g/200g weight, group K4 received HFD with intervention of sweet orange at a dose of 9ml/200g weight, and K5 group receiving HFD with intervention of red dragon fruit at a dose of 3.6g/200g weight. Compared to Pre-test, Group K3, K4 and K5 had an average change of CRP levels at post-test: -1.30±0.08mg/L, -1.39±0.04 mg/L and -1.48±0.09 mg/L respectively. All samples resulted in reduction of CRP levels in Sprague-Dawley rats with Red dragon fruit showed greater effect compared to other fruits.